Methods of determination of initial level of students' knowledges on basic disciplines at higher medical educational institutions - Ihor Chovpan (ScienceRise: Pedagogical Education, 2017)
Authors propose the program, which determines the input level of knowledge of students in Ukraine medical schools with English as the language of studying. It assesses the level of residual knowledge in mathematics, physics and English and also gives recommendations for teaching in the group, taking into account the characteristics of specific educational group. The program allows the teacher to build a more successful educational process, which in the end, improves the overall result. For testing the students and teacher should be provided with personal computers with operational system Windows 98 and higher or Linux OS with graphical interface and support the Wine program. The questions (in English) pre-installed in the testing program and correspond to the program in physics of high school and to basic mathematical course. English questions do not include grammar checking, but created to check the meaning of written text and basic vocabulary. A significant advantage of the program is the ability to add and reduce the number of questions in the test, in case of, for example, lack of time, and teachers can change the questions themselves. The beginning and the end of the test set by the teacher. The program allows the teacher to build a more successful educational process, which improves the overall result